Physical activity, nutrition, and dyslipidemia in middle-aged women - Delavar, Mouloud Agajani; Lye, Munn Sann; Syed Hassan, Syed Tajuddin; Khor, Geok Lin; Hanachi, Parichehr (Tehran University of Medical Sciences, 2011)
Background: Cardiovascular disease is a major cause of death throughout the world. The aim of this study was to assess the prevalence of overweight/obesity, central obesity, hypertension and dyslipidemia, as well as dietary factors contributing to the development of dyslipidemia among middle-aged women. Methods: The research design of the present study was a population-based cross-sectional study; anthropometric measures and blood chemistry were obtained. Physical activity was measured using the original International Physical Activity Questionnaires Long Form while food frequency questionnaire (FFQ) was used in assessing individual's habitual intake. Overall, 809 women, 30-50 years of age from fourteen active urban Primary Healthcare Centers (PHC) in Babol City, northern Iran, were obtained from 1,905 households across operational areas of 14 PHC using systematic random sampling method. Results: The prevalence rates of women classified as overweight/obese, with central obesity, hypertension and dyslipidemia were 82.8%, 75.5%, 14.6% and 63.4%, respectively. Total physical activity did not correlate with cholesterol ratio. Soybean protein was inversely associated with cholesterol ratio (rho=-0.18, P≤ 0.001). The adjusted OR for dyslipidemia in women with moderate protein intake was significantly higher than in women with high and low intake (OR=2.31; 95% CI= 1.61, 3.30). No significant associations were found between dyslipidemia and carbohydrate, fat intake or physical activity. Conclusion: This study showed very high prevalence of cardiovascular disease risk factors among Iranian middle-aged women. A more detailed study is suggested to develop definitively recommendations for the primary and secondary prevention of cardiovascular disease for the Iranian population.